Measurement of quality parameters of Snakehead Fish (Channa striata) simplicia from sungai Itik village, West Kalimantan - Wintari Taurina; Mohamad Andrie (Pharmaciana, 2023)
Snakehead fish (Channa striata) is one of the natural ingredients that have the potential to heal wounds quickly. Snakehead fish extract ointment with a combination of kelulut honey, clove oil, golden sea cucumber extract, and green betel extract can accelerate wound healing. Standardization is a process carried out to ensure the stability, safety, quality, and efficacy of the natural ingredients used. This study aims to standardize simplicia (fish fillet) raw materials used for the manufacture of snakehead fish extract herbal ointment. The method used follows the Indonesian National Standard, samples were sent to LPPT UGM and Baristand Pontianak. The results of the simplicia (fish fillet) test for snakehead fish were 81.6% water content, 0.813% total ash content, 0.02% acid-insoluble ash content, 19.3% protein, 2.93% total fat, 0.01% iron mg/kg, zinc 0.002 mg/kg, and calcium 817 mg/kg and the alkaloid and tannin quality tests were negative. the results of the simplicia test (fish fillet) for snakehead fish E. coli 3 AMP/gr, ALT 3.2 x 104 colonies/g, and the Salmonella test also met the requirements. The results of characterization tests with various methods and parameters that have been carried out show that the simplicia (fish fillet) of snakehead fish (Channa striata) has good quality and quality to be processed into extracts.